Acute nasal pro-inflammatory response to air pollution depends on characteristics other than particle mass concentration or oxidative potential: the RAPTES project - Steenhof, Maaike; Mudway, Ian S; Gosens, Ilse; Hoek, Gerard; Godri, Krystal J; Kelly, Frank J; Harrison, Roy M; Pieters, Raymond H H; Cassee, Flemming R; Lebret, Erik; Brunekreef, Bert A; Strak, Maciej; et al. (Occupational and environmental medicine (London, England), 2013)
Objectives To investigate which air pollution characteristics are associated with biomarkers for acute nasal airway inflammation in healthy subjects. We hypothesised that associations would be strongest for oxidative potential (OP) of particles. Methods 31 volunteers were exposed to ambient air pollution at five sites in The Netherlands: two traffic sites, an underground train station, a farm and an urban background site. Each subject visited at least three sites between March and October 2009 and was exposed for 5 h per visit including exercise for 20 min every hour (h). Air pollution measurements during this 5-h-period included particulate matter (PM) mass concentration, elemental composition, elemental and organic carbon (OC), particle number concentration, OP, endotoxins, O3 and NO2. Pro-inflammatory biomarkers were measured before, 2 and 18 h postexposure, including cytokine IL-6 and IL-8, protein and lactoferrin in nasal lavage (NAL) as well as IL-6 in blood. One- and two-pollutant mixed models were used to analyse associations between exposure and changes in biomarkers. Results In two-pollutant models, cytokines in NAL were positively associated with OC, endotoxin and NO2; protein was associated with NO2; and lactoferrin was associated with all PM characteristics that were high at the underground site. In blood, associations with OC and endotoxin were negative. Conclusions We observed no consistent effects in two-pollutant models for PM mass concentration and OP. Instead, we found consistent associations with nasal inflammatory markers for other PM characteristics, specifically OC, endotoxin and NO2.